2023
DOI: 10.1136/jitc-2023-006678
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment of unresectable or metastatic HER2 positive esophagogastric adenocarcinoma: liquid biomarker analysis of the phase 2 INTEGA trial

Abstract: BackgroundThe addition of nivolumab to trastuzumab and chemotherapy in first-line unresectable or metastatic HER2 positive esophagogastric adenocarcinoma (HER2+ EGA) results in long progression-free and overall survival as shown by the INTEGA (ipilimumab or FOLFOX in combination with nivolumab and trastuzumab in HER2 positive esophagogastric adenocarcinoma) trial. This trial suggested that the chemotherapy backbone is needed in an unselected HER2+ patient population. Yet, it remains an open question if there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Tumor-infiltrating lymphocyte (TiL) repertoires will be determined by next-generation sequencing (NGS) of the T-cell receptor beta (TCRβ) and immunoglobulin heavy locus (IGH). In previous studies, the diversification of T cells during therapy or TiL clone expansion in the peripheral blood was associated with response to immunotherapies ( 25 , 26 ). Resistance to HER2-targeting in HER2-positive tumors might be already present at time of first diagnosis or will eventually develop during antitumor treatment.…”
Section: Introductionmentioning
confidence: 93%
“…Tumor-infiltrating lymphocyte (TiL) repertoires will be determined by next-generation sequencing (NGS) of the T-cell receptor beta (TCRβ) and immunoglobulin heavy locus (IGH). In previous studies, the diversification of T cells during therapy or TiL clone expansion in the peripheral blood was associated with response to immunotherapies ( 25 , 26 ). Resistance to HER2-targeting in HER2-positive tumors might be already present at time of first diagnosis or will eventually develop during antitumor treatment.…”
Section: Introductionmentioning
confidence: 93%
“…The function of this checkpoint acts as a "don't-find-me" signal to the adaptive immune response [170]. PD-L1 has been established as a predictive biomarker of the response to PD-L1/PD-1 inhibitors [171]. However, it is reported that >50% patients with high PD-L1 expression in tumor tissue do not benefit from first-line Pembrolizumab [172], and 10% of patients with a PD-L1 negative tumor do respond to second-line inhibitors [173].…”
Section: Pd-l1 Determinationmentioning
confidence: 99%
“…However, some studies have shown that determination of PD-L1 expression in CTCs is not useful to predict treatment outcome. In the phase 2 INTEGA trial conducted on esophagogastric patients, PD-L1 expression on CTCs using CellSearch was not associated with a specific outcome in the Ipi arm (Trastuzumab and Nivolumab in combination with Ipilimumab) [171]. In metastatic renal cell carcinoma patients, Bootsma et al focused on the expression of PD-L1 and HLA-I in CTCs, captured and enriched using a versatile exclusion-based rare sample analysis (VERSA).…”
Section: Pd-l1 Determinationmentioning
confidence: 99%